SARS‐CoV2 (COVID‐19) infection: is fetal surgery in times of national disasters reasonable?. (22nd April 2020) - Deprest, Jan; Van Ranst, Marc; Lannoo, Lore; Bredaki, Emma; Ryan, Greg; David, Anna; Richter, Jute; Van Mieghem, Tim
Abstract: Even though the global COVID‐19 pandemic may affect how medical care is delivered in general, most countries try to maintain steady access for women to routine pregnancy care, including fetal anomaly screening. This means that, also during this pandemic, fetal anomalies will be detected, and that discussions regarding invasive genetic testing and possibly fetal therapy will need to take place. For patients, concerns about Severe Acute Respiratory Syndrome‐Corona Virus 2 will add to the anxiety caused by the diagnosis of a serious fetal anomaly. Yet, also for fetal medicine teams the situation gets more complex as they must weigh up the risks and benefits to the fetus as well as the mother, while managing a changing evidence base and logistic challenges in their healthcare system.